Understanding and Undoing the Legacies of Sexual Violence in India, USA and the World. Issue 1 (June 2017) - Gupta, Ruchira
The essay explores the historical colonial legacies of prostitution, sexual and gendered violence. It draws parallels with new forms of colonialism by mining, timber, oil, and other extractive industries that destroy families and eco-systems at the same time. It connects how violence is deliberately engendered to destroy and colonize whole communities and societies. The essay attempts to show that sexual violence and structural violence are interlinked and that to undo the systems of structural violence, women and men will have to confront the sexual violence in their lives as individuals, as collectives and in systems.